Tsetse and trypanosomosis in Africa: the challenges, the opportunities - Ilemobade, A A (Onderstepoort journal of veterinary research, 2009)
Tsetse-fly and the disease it transmits, trypanosomosis, remain an enormous disease challenge in the 37 countries of sub-Saharan Africa where the impact continues to be manifest in disease burden, increased level of poverty and decreased agricultural productivity. The impact also extends over an estimated 10 million km2 (a third of the African continent) of land area, a third of which contains some well-watered part of the continent, thus denying humans and livestock of potentially rich arable and pastureland. The disease is a threat to an estimated 50 million people and 48 million cattle with estimated annual losses in cattle production alone of 1-1.2 billion US$. These losses are due to stock mortality and depressed productivity, which may be of meat, milk, reproduction or traction. Beyond its direct effects on humans and livestock is its impact on African agriculture and the livelihood of the rural population in the affected countries: the fly and the disease influence where people decide to live, how they manage their livestock, and the intensity and the mix of crop agriculture. The combined effects result in changes in land use and environment which may, in turn, affect human welfare and increase the vulnerability of agricultural activity. Trypanosomosis is, therefore, both a public health and an agricultural development constraint. The challenges that the elimination or control of tsetse fly and trypanosomosis pose as well as the opportunities to develop appropriate intervention technologies are discussed in this presentation.